Petrous Apex Cholesterol Granuloma Showing 68Ga-DOTATATE Uptake - (:unkn) unknown (NLM (Medline), 2021)
ABSTRACT: The importance of 68Ga-DOTATATE PET/CT in the evaluation of neuroendocrine tumors is well established. However, false-positive results can occur due to inflammatory pathologies. We report a 47-year-old man who was diagnosed with a neuroendocrine tumor of the stomach. Initial 68Ga-DOTATATE PET/CT showed intense 68Ga-DOTATATE uptake in the petrous apex. Histopathological confirmation could not be obtained, thus the asymptomatic patient was followed with periodic clinical/radiologic examinations for more than 2.5 years. Therefore, this lesion was diagnosed as a cholesterol granuloma of the temporal bone. These results suggested that an initial wait-and-scan approach is a feasible management strategy for similar presentations. Copyright © 2021 Wolters Kluwer Health, Inc. All rights reserved.